PERCEIVED VERSUS REALIZED BENEFITS IN E-COMMERCE ADOPTION - Pauline, Ratnasingam (Malaysian Journal of Library and Information Science, 2002)
The Internet has revolutionized the capacity to share information across organizations, resulting in radical transformations of organizational practices for procuring supplies, delivering goods and services, and carrying out financial transactions. Organizations around the world are capitalizing on new technologies such as the Internet and World Wide Web to develop e-business. Evolving e-business models, integrated solutions and improved technological infrastructures are continuously changing the way businesses are conducted. Despite the hype of the Internet for e-business, the benefits realized from e-commerce adoption among firms are unclear in terms of perceived versus realized benefits. Using case studies in three organizations the writer examines the impact of perceived versus realized benefits in e-commerce adoption. The findings reveal that the type and focus of perceived versus realized benefits is unique for each organization. The paper also discusses the implications of this study to theory and practice including the lessons learned by these organizations.